COMPARATIVE ANALYSIS OF RENAL PROFILE AND SERUM ELECTROLYTES AMONG DIABETIC AND NON DIABETIC GROUPS IN DISTRICT PESHAWAR KP - ABDULLAH, .; AMIN, FE; KHAN, K; REHMAN, A; SHAH, SJA; AZAM, MK; REHMAN, AU; KHAN, F (Biological and Clinical Sciences Research Journal, 2024)
Diabetes mellitus is a prevalent non-communicable disease worldwide, contributing significantly to morbidity and mortality. Renal complications are a significant concern in diabetes, with hyperglycemia exacerbating renal dysfunction. Objective: This study aimed to assess renal function and electrolyte balance in diabetic and non-diabetic individuals, focusing on serum urea, creatinine levels, and electrolyte imbalances. Methods: This study was conducted at Al-Khidmat Hospital and processed at the MLT Skill Lab at Abasyn University, Peshawar. A total of 100 participants were enrolled, including diabetic and non-diabetic subjects. Blood samples were collected using a questionnaire design. Renal function tests (RFTs) were analysed using a biochemistry analyser, and serum electrolytes were assessed using an Electrolytes Analyzer. Data collection duration, methodology, and statistical analysis methods were employed. Results: Among the participants, individuals aged 40 to 70 in both genders exhibited a higher prevalence of elevated urea and creatinine levels, particularly in diabetic patients. Diabetic individuals showed a significant association with azotemia. Electrolyte imbalances, notably hypokalemia, were observed, indicating potential complications in diabetic patients. Conclusion: The study highlights the importance of proactive management strategies to mitigate renal complications in diabetic individuals. Comprehensive monitoring of renal function and electrolyte balance is essential in clinical practice.